Bioclickable Mussel-Derived Peptides With Immunoregulation for Osseointegration of PEEK - Huan Zhao; Xiaokang Wang; Xiaokang Wang; Wen Zhang; Lin Wang; Can Zhu; Yingkang Huang; Rongrong Chen; Xu Chen; Miao Wang; Guoqing Pan; Qin Shi; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Polyether ether ketone (PEEK)–based biomaterials have been widely used in the field of spine and joint surgery. However, lack of biological activity limits their further clinical application. In this study, we synthesized a bioclickable mussel-derived peptide Azide-DOPA4 as a PEEK surface coating modifier and further combined bone morphogenetic protein 2 functional peptides (BMP2p) with a dibenzylcyclooctyne (DBCO) motif through bio-orthogonal reactions to obtain DOPA4@BMP2p-PEEK. As expected, more BMP2p can be conjugated on PEEK after Azide-DOPA4 coating. The surface roughness and hydrophilicity of DOPA4@BMP2p-PEEK were obviously increased. Then, we optimized the osteogenic capacity of PEEK substrates. In vitro, compared with the BMP2p-coating PEEK material, DOPA4@BMP2p-PEEK showed significantly higher osteogenic induction capability of rat bone marrow mesenchymal stem cells. In vivo, we constructed a rat calvarial bone defect model and implanted PEEK materials with a differently modified surface. Micro-computed tomography scanning displayed that the DOPA4@BMP2p-PEEK implant group had significantly higher new bone volume and bone mineral density than the BMP2p-PEEK group. Histological staining of hard tissue further confirmed that the DOPA4@BMP2p-PEEK group revealed a better osseointegrative effect than the BMP2p-PEEK group. More importantly, we also found that DOPA4@BMP2p coating has a synergistic effect with induced Foxp3+ regulatory T (iTreg) cells to promote osteogenesis. In summary, with an easy-to-perform, two-step surface bioengineering approach, the DOPA4@BMP2p-PEEK material reported here displayed excellent biocompatibility and osteogenic functions. It will, moreover, offer insights to engineering surfaces of orthopedic implants.